995. Safety and Efficacy of F/TAF and F/TDF for PrEP in DISCOVER Participants Taking F/TDF for PrEP at Baseline. (31st December 2020) - Campbell, Thomas; Clarke, Amanda; Trottier, Benoit; Carter, Christoph C; Shao, Yongwu; Ebrahimi, Ramin; Das, Moupali; Brainard, Diana M; Gladstein, Jay
Abstract: Background: DISCOVER is an ongoing trial comparing emtricitabine plus tenofovir alafenamide (F/TAF) or tenofovir disoproxil fumarate (F/TDF) for HIV pre-exposure prophylaxis (PrEP). DISCOVER included some participants already taking F/TDF for PrEP at baseline (BL) creating a unique opportunity to study outcomes after switching from F/TDF to F/TAF. Methods: Men who have sex with men and transgender women at risk of HIV were randomized to receive blinded daily F/TAF or F/TDF and followed for at least 96 weeks; participants taking BL F/TDF for PrEP could enroll without a washout period. Laboratory assessments included estimated glomerular filtration rate (eGFR), markers of renal proximal tubular function (RBP and β2M to creatinine ratios), and fasting cholesterol levels; these were analyzed by 2-sided Wilcoxon rank sum test. Bone mineral density (BMD) was assessed in a subset of participants and analyzed by ANOVA. Results: 905 of 5387 (16.8%) participants were on BL F/TDF for PrEP for a median duration of 399 days; baseline characteristics are found in Table 1. There was one HIV infection among BL PrEP users, in a participant randomized to F/TDF who had intermittent low adherence. Participants on BL PrEP randomized to F/TAF had improvements in eGFR and markers of proximal tubular function compared to F/TDF. Median change in BMD was not statistically different for BL PrEP users assigned to F/TAF vs F/TDF, however de novo F/TAF participants had improved BMD profiles compared to F/TDF. BL PrEP users in the F/TAF arm had increases in LDL cholesterol (median +6mg/dL) compared to F/TDF, while changes in HDL and total:HDL ratio were similar. Lipid-modifying agent (LMA) initiation in BL PrEP users was more frequent in the F/TAF arm, while LMA initiation in de novo PrEP participants was similar between arms (Table 2). Table 1. Characteristics of DISCOVER participants Table 2. Efficacy and safety results Conclusion: HIV incidence was low in participants taking BL PrEP. Participants who switched from F/TDF to F/TAF had improvements in renal biomarkers. There was no statistical difference in BMD among BL PrEP users, although numbers were small. The observed lipid changes in BL PrEP users are consistent with the LDL and HDL suppressive effect of TDF, and the small but higher rate of LMA initiation with F/TAF is likely related to withdrawal of this effect. Disclosures: Thomas Campbell, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Amanda Clarke, MD, Gilead Sciences Inc. (Consultant, Scientific Research Study Investigator, Other Financial or Material Support, Conference attendance sponsorship)Viiv Healthcare (Consultant, Other Financial or Material Support, Conference travel sponsorship) Benoit Trottier, MD, AbbVie (Grant/Research Support, Other Financial or Material Support, Personal fees)Bristol-Myers Squibb (Grant/Research Support, Other Financial or Material Support, Personal fees)Gilead Sciences Inc. (Grant/Research Support, Scientific Research Study Investigator, Other Financial or Material Support, Personal fees)Janssen (Grant/Research Support, Other Financial or Material Support, Personal fees)Merck (Grant/Research Support, Other Financial or Material Support, Personal fees)Viiv Healthcare (Grant/Research Support, Other Financial or Material Support, Personal fees) Christoph C. Carter, MD, Gilead Sciences Inc. (Employee, Shareholder) Yongwu Shao, PhD, Gilead Sciences Inc. (Employee, Shareholder) Ramin Ebrahimi, MSc, Gilead Sciences Inc. (Employee, Shareholder) Moupali Das, MD, Gilead Sciences Inc. (Employee, Shareholder) Diana M. Brainard, MD, Gilead Sciences (Employee) Jay Gladstein, MD, Gilead Sciences Inc. (Scientific Research Study Investigator)